Thermal Annealing Effects of Molybdenum Oxide Interfacial Layer Based on Organic Solar Cells - Baek, Jinho; Kang, Nam Su; Lee, Yang Doo; Kang, Byung Hyun; Dong, Ki-Young; Lim, Jung Ah; Song, Yong-Won; Hong, Jae-Min; Ju, Byeong-Kwon (AMER SCIENTIFIC PUBLISHERS, 2013)
Organic photovoltaic (OPV) cells were fabricated with a molybdenum oxide (MoOx) interfacial layer instead of a PEDOT:PSS layer to improve power conversion efficiency (PCE) and long-term stability. Physical parameters of organic solar cells such as fill factor, current density, and open circuit voltage were changed to improve efficiency by transforming the crystal structure of the molybdenum oxide interfacial layer through thermal annealing PEDOT:PSS has been known to cause acid etching problems on the ITO which degrades the device's overall longevity. Additionally, we have confirmed that when various thermal annealing conditions were applied to the molybdenum oxide layer, the fill factor and current density were continuously improved. In our experiments, the device with a thermal annealing temperature of 250 degrees C for 30 minutes exhibited a PCE of 3.18% under AM 1.5G illumination.